Research of effective teaching methodologies of drawing lessons - Zokirova Shahlokhon (Zeta Repository, 2023)
since drawing is the main skill for the expression of creativity, it is very important that teachers adopt effective teaching methodologies to make the learning process more accessible and interesting for students. In this dissertation, we will study the necessary aspects of an effective teaching methodology for drawing lessons. We will look at the traditional and modern directions of teaching drawing, identify important components of effective teaching methodology and cite examples of successful teaching methods. In addition, we will consider factors that can affect the effectiveness of educational methodologies, such as lesson size, student motivation, the teacher’s personal approach to education.